Obligations of Consecrated Life Institute towards its members - SZEWCZUL, BOŻENA (Prawo Kanoniczne, 2014)
When we analyse the norms of the Canonical Law Code 1983 we can see, that religious has a right to expect from the Institute – through his superiors – that he will be provided with necessary spiritual and material means required for realization of the calling obtained from God, in order to be able to truly imitate the Christ – God and Man. However it seams, that especially during last years, human factor of the help, that is a question of human dignity of consecrated people, has been seriously neglected during so called monastery formation. Nevertheless it seams to be logical, that the deficiency of human formation also results the invalid formation of the two consecutive stages, that is Christian and monastic formation, since it is well known that God builds upon the human nature. Immature and „defective” Man-monk, who gives up his human dignity will never be able to achieve fully his vocation for sanctity, when lives in monastery institute, which does not fulfill its duties toward his members.